The influence of physical environmental factors of Bima stilt house on pulmonary tuberculosis of Acid Fast Bacillii positive in Bima, Province of West Nusa Tenggara - Elya Antariksana Bachmida; Yusrizal Djam’an Saleh; Titik Nuryastuti (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Physical environment factors of stilt houses affecting incidence of pulmonary tuberculosis in the district of Bima, West Nusa TenggaraPurposeThis research aimed to determine factors in the physical environment of typical houses on stilts affecting the incidence of pulmonary tuberculosis acid fast bacilli positive in the district of Bima, West Nusa Tenggara. MethodsThis study used a matched case control design to examine the relationship between specific effects with certain risk factors. There were 76 total respondents, with 38 in the case group and 38 in the control group. ResultsBivariate analysis showed that residential density (p=0.001; OR= 5.7), lighting in bedroom (p=0.029; OR=32), nutritional status (p=0.029; OR=3.2) were statistically associated with the incidence of smear-positive pulmonary tuberculosis at typical stilt houses in Bima. The most dominant risk factor in the incidence of smear-positive pulmonary tuberculosis in typical Bima stilts houses was the residential density.ConclusionResidential density, natural lighting in bedrooms were not risk factors, while malnutrition status increased the probability for prevalence of pulmonary tuberculosis acid fast bacilli positive in houses on stilts typical in the district of Bima.